2022
DOI: 10.1155/2022/4463294
|View full text |Cite|
|
Sign up to set email alerts
|

Anticancer and Anti-Inflammatory Mechanisms of NOSH-Aspirin and Its Biological Effects

Abstract: NOSH-Aspirin, which is generated from NO, H2S, and aspirin, affects a variety of essential pathophysiological processes, including anti-inflammatory, analgesic, antipyretic, antiplatelet, and anticancer properties. Although many people acknowledge the biological significance of NOSH-Aspirin and its therapeutic effects, the mechanism of action of NOSH-Aspirin and its regulation of tissue levels remains obscure. This is in part due to its chemical and physical features, which make processing and analysis difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%